If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2y + 2z = 70 Solving x + 2y + 2z = 70 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. x + 2y + -2y + 2z = 70 + -2y Combine like terms: 2y + -2y = 0 x + 0 + 2z = 70 + -2y x + 2z = 70 + -2y Add '-2z' to each side of the equation. x + 2z + -2z = 70 + -2y + -2z Combine like terms: 2z + -2z = 0 x + 0 = 70 + -2y + -2z x = 70 + -2y + -2z Simplifying x = 70 + -2y + -2z
| 16x-3=9+5x | | x+2x=2x+30 | | 5m-(6w+9)=11 | | 7-3x=5x+19 | | 5p-7=4p+3 | | 4m-5=6m+d | | (2x+1)+y=56 | | 16-3p=-21 | | 110+(3x-20)=180 | | 4x+12+34=180 | | 9x-8y=16 | | x^3-5x^2+2x+10=0 | | x^3-5x+2x^2+10=0 | | x^3-15=39 | | 12+x-x^2= | | 20-x-x^2= | | 14-5x-x^2= | | 9(x-4)+2(1+4x)=0 | | 12+4x-x^2= | | 2a-10=-8 | | 5-4x-x^2= | | -5(-3-x)-12=3(1+11x) | | 4x+7=6x-2 | | -11+8x=5x+7 | | 2x-45=15 | | -4x+-3(x-5)=8x | | 8+2x-x^2= | | 8x-9=8(x-1)+1 | | 2x-21x+20=0 | | 5+6d=10+1d | | 64.00+x=67.68 | | 10(x+7)=10(x+11) |